Mercury in the snow and firn at Summit Station, Central Greenland, and implications for the study of past atmospheric mercury levels - X. Faïn (Atmospheric Chemistry and Physics, 2008)
Gaseous Elemental Mercury (Hg° or GEM) was investigated at Summit Station, Greenland, in the interstitial air extracted from the perennial snowpack (firn) at depths ranging from the surface to 30 m, during summer 2005 and spring 2006. Photolytic production and destruction of Hg° were observed close to the snow surface during summer 2005 and spring 2006, and we observed dark oxidation of GEM up to 270 cm depth in June 2006. Photochemical transformation of gaseous elemental mercury resulted in diel variations in the concentrations of this gas in the near-surface interstitial air, but destruction of Hg° was predominant in June, and production was the main process in July. This seasonal evolution of the chemical mechanisms involving gaseous elemental mercury produces a signal that propagates downward through the firn air, but is unobservably small below 15 m in depth. As a consequence, multi-annual averaged records of GEM concentration should be well preserved in deep firn air at depths below 15 m, and available for the reconstruction of the past atmospheric history of GEM over the last decades.